sec(2x) = [sec^2(x)] / [2 - sec^2(x)]
Your first step would be to choose the more complex side. I'm going to choose the right hand side (RHS).
RHS = [sec^2(x)] / [2 - sec^2(x)]
Now, I'm going to convert everything to sines and cosines.
RHS = [1/cos^2(x)] / [2 - 1/cos^2(x)]
Multiplying the top and bottom by cos^2(x), we get
RHS = 1 / [2cos^2(x) - 1]
There's an identity out there called the half angle identity, which goes as follows:
cos(2y) = cos^2(y) - sin^2(y) = 1 - 2sin^2(y) = 2cos^2(y) - 1
Using the third form of the identity,
RHS = 1 / cos(2x)
Which, by definition is equal to
RHS = 1 / cos(2x) = sec(2x) = LHS
2007-01-01 14:11:09
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
Start by rewritting the secant function in terms of the cosine function.
sec(2x)=1/cos(2x)
Then use the trigonometric identity cos(2x) = cos^2(x) - sin^2(x) = 2 cos^2(x) - 1 = 1 - 2 sin^2(x).
For the right side, sec^2x =1/cos^2x. Then use the trig identity of cos^2(x) = 1/2 + 1/2 cos(2x).
Essentially just use the above and whole lot of algebra to get the same expression on each side.
2007-01-01 14:18:47
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
Prove the identity.
sec2x = (sec² x)/(2 - sec² x)
Let's work with the right hand side (RHS) to show it is the same as the left.
Remember sec x = 1/cos x.
Remember also the double angle formula cos(2x) = 2cos² x - 1.
RHS = (sec² x)/(2 - sec² x)
Now multiply numerator and denominator by cos² x.
= 1/(2cos²x - 1)
Now apply the double angle formula.
= 1/cos(2x)
= sec(2x) = left hand side.
2007-01-01 14:20:36
·
answer #3
·
answered by Northstar 7
·
0⤊
0⤋
Start with the right-hand side:
(sec^2x)/(2 - sec^2x) = 1/(cos^2x) * 1/(2 - 1/(cos^2x))
Multiply the two fractions:
= 1 / (2cos^2x - 1)
Note that 1 = cos^2x + sin^2x:
= 1 / (cos^2x + cos^2x - cos^2x - sin^2x)
= 1 / (cos^2x - sin^2x)
= 1 / (cos2x)
= sec2x
QED
2007-01-01 14:15:10
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Soul Train
2016-05-23 04:45:10
·
answer #5
·
answered by Victoria 4
·
0⤊
0⤋
I am super math stupid but you can find help with this by plugging the equation into a google window and hit return.
2007-01-01 14:15:59
·
answer #6
·
answered by skyboy96 1
·
0⤊
0⤋
sec(2x) = (sec(x)^2)/(2 - sec(x)^2)
sec(2x) = 1/(cos(2x)) =
1/(cos(x)^2 - sin(x)^2), 1/(2cos(x)^2 - 1), or 1/(1 - 2sin(x)^2)
(sec(x)^2)/(2 - sec(x)^2)
(1/cos(x)^2)/(2 - (1/cos(x)^2))
(1/cos(x)^2)/((2cos(x)^2 - 1)/(cos(x)^2))
(1/cos(x)^2) * ((cos(x)^2)/(2cos(x)^2 - 1))
(cos(x)^2)/((cos(x)^2)(2cos(x)^2 - 1))
1/(2cos(x)^2 - 1)
sec(2x)
so
sec(2x) = (sec(x)^2)/(2 - sec(x)^2)
2007-01-01 15:30:08
·
answer #7
·
answered by Sherman81 6
·
0⤊
0⤋